Is there a nonlinear long-run relation in the U.S. interest rate and inflation? - lee, Hwa-tae; Khim-Sen Liew, Venus; Gawon, Yoon (Economics Bulletin, 2013)
Recent advances in nonlinear cointegration analysis find evidence for a nonlinear long-run relation between the U.S. interest rate and inflation. Employing the Breitung's (2001) rank tests for nonlinear cointegration, we find herein little evidence for cointegration in the U.S. data. We also provide simulation results regarding the performance of the rank tests for some plausible nonlinear models for the data.